PENGARUH EKSTRAK KELOPAK BUNGA ROSELLA (HIBISCUS SABDARIFFA) TERHADAP MORFOLOGI SPERMATOZOA PADA TIKUS JANTAN PUTIH GALUR WISTAR (RATTUS NORVEGICUS) YANG DIBERIKAN PAPARAN ASAP ROKOK - Rizka Safira Ayu Astadewi (2020)
Smoking is an unhealthy lifestyle, but it can be found in our life. Smoking has a negative impact on health problems, quality, and quantity of sperm. Rosella contains flavonoid and vitamin C which act as an antioxidant, which is suspected that antioxidants can improve the quality of spermatozoa or the process of spermatogenesis. This study aimed to determine the effect of Roselle (Hibiscus Sabdariffa) extract on spermatozoa of wistar strain (Rattus norvegicus) exposed to cigarette smoke. This study was conducted for 52 days and 7 days of acclimatization, using an experimental research design with samples of roselle extract at a dose of 270 mg/kgBW and 540 mg/kgBW. The sample for each group needed in this study was 7 rats, there were 4 different treatment groups so that the total sample required was 28 rats. The sample was divided into 4 treatment groups, negative control, positive control, a group of rats who were given roselle extract 270 mg/kgBW and exposed to 2 sticks/day cigarette smoke, and a group of rats who were given roselle extract 540mg/kgBW and given exposure to 2 sticks/day cigarette smoke. The average percentage of abnormal morphology in the negative control group was 14.57%, the positive control was 27.29%, the treatment (1) was 28.29%, the treatment (2) was 24.29%. After tested by One Way Anova method, it showed a P value of 0.001 (P <0.05) which could be concluded that there was an effect of giving roselle extract on spermatozoa morphology of wistar rats exposed to cigarette smoke